Cognitive Rehabilitation in Parkinson’s Disease: Evidence from Neuroimaging - Nombela, Cristina; Bustillo, Pedro J.; Castell, Pedro; Medina, Vicente; Herrero, Maria-Trinidad (Frontiers in Neurology, 2011)
Cognitive impairment in Parkinson’s disease (PD) has received little attention and as such, there are currently very few treatment options available. The aim of the present study was to evaluate the attention impairment in PD patients and to determine whether cognitive training might alleviate any such symptoms. The study, which included a pilot and experimental phase, involved assessing performance in a modified version of the Stroop task during functional magnetic resonance imaging (fMRI). The study was carried out in ten PD patients and ten paired healthy controls, half of the PD patients undergoing 6 months of cognitive training based on Sudoku exercises. The brain training programme improved the cognitive performance of the Parkinson’s patients in attention tasks and it provoked comparable patterns of cortical activation to those observed in controls. Based on these findings, we propose that cognitive training can contribute significantly to save brain resources in PD patients, maybe by readdressing the imbalance caused by the alterations to inhibitory circuitry.